IRIS RECOGNITION FAILURE IN BIOMETRICS: A REVIEW - Zainal Abidin, Zaheera; Manaf, Mazani; Shibghatullah, Abdul Samad; Anawar, Syarulnaziah (2014)
More than twenty years iris has been claimed to be the most stable modality in human lifetime. However, the iris recognition produces ‘failure to match’ problem which made the known is unknown user or the genuine is recognized as imposter in the biometric systems. Apparently, failure to recognize the real user as in the database is due to a few assumptions: aging of the sensor, changes in how a person uses the system such as the threshold settings and template aging effect. This paper focuses on template aging effect since it is on ongoing problem faced in iris recognition. Many studies attempted several techniques to overcome the problem in every phase which consists of three general phases: the pre-processing, feature extraction and feature matching. Therefore, the purpose of this paper is to study and identify the problems in iris recognition that lead to failure-to-match in biometrics.